2021
DOI: 10.1128/jvi.01165-21
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Requires Phosphatidylserine Scrambling Activity for Efficient Budding and Optimal Infectivity

Abstract: Ebola virus (EBOV) attaches to target cells using two categories of cell surface receptors, C-type lectins and phosphatidylserine (PS) receptors. PS receptors typically bind to apoptotic cell membrane PS and orchestrate the uptake and clearance of apoptotic debris. Many enveloped viruses also contain exposed PS and can therefore exploit these receptors for cell entry. Viral infection can induce PS externalization in host cells, resulting in increased outer PS levels on budding virions. Scramblase enzymes carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…VSV represents a valuable vaccine platform thanks to its ability to replicate at high titers, its low seroprevalence, and little pre-existing immunity in humans. VSV-based vaccines are produced through transfection of mammalian cells including baby hamster kidney cells stably expressing T7 polymerase (BHK-T7) or HEK293T with a recombinant VSV plasmid expressing the transgene of interest in place of the virus’ G gene 55 (Fig. 3 ).…”
Section: Vesicular Stomatitis Vector Vaccinesmentioning
confidence: 99%
“…VSV represents a valuable vaccine platform thanks to its ability to replicate at high titers, its low seroprevalence, and little pre-existing immunity in humans. VSV-based vaccines are produced through transfection of mammalian cells including baby hamster kidney cells stably expressing T7 polymerase (BHK-T7) or HEK293T with a recombinant VSV plasmid expressing the transgene of interest in place of the virus’ G gene 55 (Fig. 3 ).…”
Section: Vesicular Stomatitis Vector Vaccinesmentioning
confidence: 99%
“…Some viruses also modulate cellular calcium signaling pathways to increase cytosolic calcium levels, which would trigger calcium-activated scramblases [36]. Studies examining EBOV PtdSer levels have implicated both apoptotic scramblase XKR8 [37,38] and calcium-activated scramblase TMEM16F [39] in EBOV envelope PtdSer and infectivity.…”
Section: Entry Through Apoptotic Mimicrymentioning
confidence: 99%
“…While investigating the role of scramblase XKR8 in EBOV entry through apoptotic mimicry, our group observed that XKR8-knockout human haploid HAP1 cells consistently released fewer recombinant vesicular stomatitis virus particles and EBOV virus-like particles (VLPs) [38]. VLP release was restored by transfecting XKR8-knockout HAP1 cells with exogenous XKR8.…”
Section: Scramblase Xkr8 and Viral Buddingmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidylserine (PS) receptors are demonstrated to facilitate infection of SARS-CoV-2 and hence have been suggested as a therapeutic target [ 37 ]. EBOV is also known to make use of the host apoptotic clearance mechanism to augment its entry into target cells by externalizing PS on its surface [ 38 , 39 , 40 ]. In both SARS-CoV-2 [ 37 ] and EBOV [ 41 , 42 ], the T cell Ig and mucin domain (TIM) family of proteins is shown to be involved in the above mentioned mechanism.…”
Section: A Comparative Look At the Pathogenic Rna Viruses—sars-cov-2 ...mentioning
confidence: 99%